Management of Malignant Biliary Obstruction - Lorenz, Jonathan M. (Seminars in Interventional Radiology, 2016)
The diagnosis of malignant biliary obstruction combines the use of clinical evaluation, diagnostic imaging, tissue sampling, and minimally invasive options with the initial goal of identifying candidates for curative resection. The most common causes of obstruction are pancreatic adenocarcinoma and cholangiocarcinoma, and most cases are too advanced for surgical options. Interventional radiologists and gastroenterologists offer palliative options for biliary drainage such as plastic stents and catheters, bare metal stents, and covered stents. This article provides an updated review of options and outcomes for the management of malignant biliary obstruction.
Keywords: biliary obstruction; cancer; percutaneous drainage; interventional radiology